Peran Serta Masyarakat Lokal Dalam Pengelolaan Daya Tarik Wisata Pura Goa Giri Putri Nusa Penida - Widiastra, Nyoman Andika; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p09, 2018)
This research is located in Pakraman Karang Sari, Village Office Suana, Nusa Penida in tourist attraction Pura Goa Giri Putri which aims to determine the function of local communities in the management of the attraction in the development and planning as a community-based tourism destination.         Data collection techniques in this study, by observation, in-depth interviews with 6 informant, and documentation study by taking a picture in the attractions of Goa Giri Putri. The data have been analyzed with descriptive qualitative data analysis techniques are broadly communicating, and systematic explanation of the data obtained in the field with the aim of obtaining a clear picture and objektif.  The result of this research is the role of local communities in the management of a tourist attraction Pura Goa Giri Putri is as pengemong / pengempon who have the responsibility to maintain and grow attractions Goa Giri Putri directly or indirectly such as participating maintain cleanliness, keeping tourist attraction Goa Giri Putri, keeping pemedek or tourists who visit and support the implementation of the current pujawali ceremony  / ceremony at Pura Goa Giri Putri with managers and other stakeholders.   Keywords : Participation, Local Communities, Management, Tourist Attraction, Community Based Tourism